The awareness of urinary tract infection management in pregnant women. A qualitative study - Budi Iman Santoso; Raymond Surya; Farah Asyuri Yasmin; Rima Irwinda (Universitas Airlangga, 2017)
Objectives: to identify knowledge, attitude, and practice of health providers including GPs and gynecologists to the implementation of the national guideline on the treatment of UTI among pregnant women.Materials and Methods: A cross-sectional study design was used. Subjects were women who attended the International Sym-posium of UTI. Questionnaires consisting ofregarding demo-graphic characteristics, knowledge, attitude, and practice were given to the subjects. The questionnaires had been tested for valid-ity and reliability by applying the Pearson correlation and Cronbach’s alpha test. Statistical analyses were performed using SPSS 23.0 for Windows.A two-tailed p value less than 0.05 was considered to be statistically significant.Results: A total of 140 subjects were recruited in this study. Of these, 104 subjects (74.3%) returned the questionnaire, and 99 subjects (70.7%) were eligible for this study. Nine (9.1%), 69 (69.7%), and 21(21.2%) subjects had good, fair, and poor know-ledge, respectively. Sixty-five (65.7%) and 64 subjects (64.6%) showed a positive attitude and had positive practice, respectively.Conclusion: Knowledge, attitude, and practice among respon-dents are good enough, despite only a few of them have read the updated guideline. Continuous medical education through online update or symposium may be one effective method to disseminate new update in guidelines.